Triple compound tablet and preparation method thereof
The triple compound tablet design addresses bictegravir's pH-dependent solubility issues by using a bictegravir sodium layer with polyvinyl alcohol and specific disintegrants, enhancing solubility and stability, thus improving patient compliance and therapeutic efficacy.
Patent Information
- Application Number
- CN202411255005.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-24
AI Technical Summary
The dissolution of bictegravir in existing triple compound tablets is significantly affected by environmental pH, leading to slow dissolution and poor solubility in near-neutral environments, which affects patient compliance.
A triple compound tablet design comprising a first layer with bictegravir sodium, polyvinyl alcohol, and specific fillers and disintegrants, and a second layer with emtricitabine and tenofovir alafenamide hemifumarate, optimized through processes like hot melt extrusion and granulation, to enhance solubility and stability.
The optimized tablet design improves bictegravir solubility in neutral conditions, maintains tablet uniformity, and enhances the stability of tenofovir alafenamide hemifumarate, resulting in improved patient compliance and therapeutic efficacy.
Smart Images

Figure BDA0005033758490000051 
Figure BDA0005033758490000061 
Figure BDA0005033758490000062
Abstract
Description
Technical Field
[0001] The present invention relates to the field of medical technology, and in particular to a triple compound tablet and a preparation method thereof. Background Art
[0002] Acquired immunodeficiency syndrome (AIDS) is a malignant infectious disease caused by the human immunodeficiency virus (HIV); HIV is an RNA virus that, after infecting host cells, attacks the human immune system and disrupts the immune balance by multiplying in large numbers and destroying CD4+T lymphocytes, thereby reducing the body's resistance and infecting other diseases, leading to various complex infections and death.
[0003] In order to solve the problem of HIV drug resistance, oral combination drugs are used to target multiple HIV proteins or different binding sites on the same protein, which can achieve long-term permanent suppression of HIV and extend the life expectancy of HIV patients. Currently, a variety of combination preparations have been approved for marketing, such as Symfi, Triumeq, Truvada, Atripla, Genvoya, Stribild, etc.
[0004] For example, Chinese patent publication number CN108348473A discloses a double-layer tablet containing bictegravir (BIC), emtricitabine, and tenofovir alafenamide, wherein the first layer contains 52.5 mg of bictegravir sodium, and the second layer contains 200 mg of emtricitabine and 28 mg of tenofovir alafenamide hemifumarate. The above-mentioned compound tablet has good bioequivalence with tablets containing 200 mg of emtricitabine and 28 mg of tenofovir alafenamide and a single-dose tablet containing 75 mg of bictegravir administered simultaneously. However, the solubility of bictegravir in the compound tablet is still greatly affected by the pH of food, and the harsh conditions for patients to take it lead to poor compliance.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The problem solved by the present invention is that the dissolution of bictegravir in the existing triple compound tablets is greatly affected by the environmental pH, and the dissolution is slow and the dissolution rate is not high in a near-neutral environment.
[0007] In order to solve the above problems, the present invention provides a triple compound tablet, comprising a first layer and a second layer, wherein the first layer comprises 50-55 parts of bictegravir sodium and a particle size D 90The invention discloses a novel nanostructured film having a thickness of 10-200 μm, 16-20 parts of polyvinyl alcohol, 220-240 parts of a filler, 20-30 parts of a disintegrant, and 2-8 parts of a lubricant. The second layer comprises 190-210 parts of emtricitabine, 25-30 parts of tenofovir alafenamide hemifumarate, 110-125 parts of a filler, 20-30 parts of a disintegrant, and 2-8 parts of a lubricant.
[0008] Preferably, the first layer comprises 51-53 parts of bictegravir sodium and has a particle size D 90 The particle size D of the first layer is 50-150 μm, 16-20 parts of polyvinyl alcohol, 225-233 parts of filler, 21-25 parts of disintegrant, and 3-6 parts of lubricant. The second layer includes 195-205 parts of emtricitabine, 26-29 parts of tenofovir alafenamide hemifumarate, 110-119 parts of filler, 24-27 parts of disintegrant, and 4-7 parts of lubricant. Preferably, the first layer includes 52 parts of bictegravir sodium and the particle size D 90 The invention discloses a novel nanostructured film having a thickness of 50-150 μm, 16-20 parts of polyvinyl alcohol, 225-233 parts of a filler, 21-25 parts of a disintegrant, and 3-6 parts of a lubricant. The second layer comprises 200 parts of emtricitabine, 28 parts of tenofovir alafenamide hemifumarate, 110-119 parts of a filler, 24-27 parts of a disintegrant, and 4-7 parts of a lubricant.
[0009] Preferably, the disintegrant is any one of sodium carboxymethyl starch, low-substituted hydroxypropyl cellulose, cross-linked sodium carboxymethyl cellulose, cross-linked polyvinylpyrrolidone, and starch. Preferably, the disintegrant is low-substituted hydroxypropyl cellulose.
[0010] Preferably, the filler includes at least one of pregelatinized starch, lactose, mannitol, sorbitol, sucrose, microcrystalline cellulose, calcium hydrogen phosphate, and sodium chloride. Preferably, the filler in the second granule is composed of sodium chloride and microcrystalline cellulose in a ratio of 1:1-3, such as 1:1.5, 1:2, 1:2.5, 1:3, etc., and the model of the microcrystalline cellulose is any one of Avicel PH101, PH102, PH103, PH112, and PH113. Preferably, the filler is composed of microcrystalline cellulose and sodium chloride in a ratio of 1:3, and the model of the microcrystalline cellulose is PH112.
[0011] Preferably, the lubricant is any one of magnesium stearate, calcium stearate, stearic acid, hydrogenated vegetable oil, stearyl palmitin, glyceryl behenate, sodium stearyl fumarate, colloidal silicon dioxide and talc.
[0012] Preferably, the total weight of the tablet is 680-720 mg / tablet. The total weight of the tablet can be 690-710 mg / tablet or 695-705 mg / tablet or 498-703 mg / tablet, such as 700 mg / tablet.
[0013] The present invention also provides a method for preparing a triple compound tablet, comprising:
[0014] S1, material handling on the first floor
[0015] The prescribed amount of bictegravir sodium and polyvinyl alcohol were ultrafinely ground to D 90 =50-150μm, mix for 5-15min, hot melt extrude at 75-80℃, cool to room temperature and crush to D 90 = first particles of 50-150 μm; the first particles, filler, disintegrant and lubricant oil are mixed for 3-10 minutes and then set aside; preferably, the temperature of the hot melt extrusion can be, for example, 76°C, 77°C, 78°C, 79°C, etc., and an appropriate amount of plasticizer, such as sorbitol, etc., can be added during hot melt extrusion according to the physical properties.
[0016] S2, material handling on the second floor
[0017] Mix the prescribed amount of emtricitabine, tenofovir alafenamide hemifumarate, filler, disintegrant, and lubricant for later use;
[0018] S3, tableting, coating
[0019] A double-layer tablet is compressed by using a mixture containing bictegravir sodium as the first layer and a mixture containing emtricitabine and tenofovir alafenamide hemifumarate as the second layer, and then dried after coating.
[0020] Preferably, step S2 comprises: mixing the prescribed amount of emtricitabine, tenofovir alafenamide hemifumarate, a filler, and a disintegrant for 8-12 minutes, and then dry granulating, and mixing with a lubricant for 3-10 minutes after granulation for standby use; or mixing 80-90% of the prescribed amount of emtricitabine and the prescribed amount of tenofovir alafenamide hemifumarate, a filler, and a disintegrant for 8-12 minutes, and then dry granulating, and mixing with a lubricant and the remaining amount of emtricitabine for 3-10 minutes after granulation for standby use.
[0021] Preferably, the coating material in step S3 accounts for 2.5-3.2% of the total weight of the tablet and the coating material is any one of hydroxypropyl methylcellulose, methylcellulose, hydroxyethyl cellulose and hydroxypropyl cellulose, for example, the coating material is Opadry II Brown 85F165072. The specific process parameters of tableting and coating in step S3 are the prior art.
[0022] Compared with the prior art, the triple compound tablets of the present invention have the following beneficial effects: 1) by selecting bictegravir sodium as the active ingredient and limiting its particle size to meet the quality requirements of dissolution and tablet uniformity, by selecting a specific disintegrant, the adsorption of bictegravir sodium can be reduced to improve the solubility under the same conditions; 2) by using polyvinyl alcohol to modify bictegravir sodium, the medium supersaturation performance of bictegravir sodium in an almost neutral water environment is significantly improved, and the final solubility is good; in addition, the modified bictegravir sodium itself has good flowability, and the tablets have good quality uniformity; 3) by improving the second layer preparation process, the contact with emtricitabine can be reduced without reducing the proportion of tenofovir alafenamide hemifumarate in the tablets; and by selecting a specific filler, the stability of tenofovir alafenamide hemifumarate can be further improved without setting a desiccant. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. The technical features in the embodiments of the present application can be combined with each other without conflict.
[0024] The tenofovir alafenamide of the present invention is generally in the form of a pharmaceutically acceptable salt, such as a monofumarate or a hemifumarate, preferably tenofovir alafenamide hemifumarate; similarly, emtricitabine may exist in a solvated or unsolvated form, preferably in the form of emtricitabine free base; bictegravir is generally in the form of a pharmaceutically acceptable salt, such as bictegravir sodium.
[0025] It should be noted that, unless otherwise specified, the dosages described in this application all refer to the amount of tenofovir alafenamide or emtricitabine or bictegravir as the active ingredient. For example, 25 mg of tenofovir alafenamide or 28 mg of tenofovir alafenamide hemifumarate have the same active ingredient, 200 mg of emtricitabine refers to 200 mg of emtricitabine free base, and 50 mg of bictegravir and 52 mg of bictegravir sodium have the same active ingredient. Polyvinyl alcohol (PVA) is a synthetic water-soluble polymer having an idealized molecular formula [CH2CH(OH)]n, good film-forming properties, adhesive properties and emulsifying properties, and a glass transition temperature of 75-85°C. Unless otherwise specified in this application, the polyvinyl alcohol refers to a 4% solution viscosity of 2-4 mPas at 20°C of 75%-85% and 2-4 mPas at 20°C, such as PVA3-80 and PVA3-83. Low-substituted hydroxypropyl cellulose refers to cellulose containing 5% to 16% hydroxypropyl substituents, which is equivalent to about 0.1 to 0.2 molar substitutions. In particular, microcrystalline cellulose refers to common models PH102 and PH103.
[0026] Tenofovir alafenamide is a weak base and is considered to be a BCS class 3 compound with high equilibrium solubility and low apparent permeability, while emtricitabine is a free base and is considered to be a BCS class 1 compound with high permeability and high solubility. Bictegravir is a weak acid and belongs to and is considered to be a BCS class 2 compound with low solubility and high permeability. The drug Biktarvy developed by Gilead consists of three active ingredients: 25 mg of tenofovir alafenamide, 200 mg of emtricitabine, and 50 mg of bictegravir. It was first launched in the United States in 2018, providing more medication options for AIDS patients. However, the solubility of bictegravir in the compound tablet is still greatly affected by the pH of food, and the conditions for taking it are harsh to achieve good efficacy, resulting in poor patient compliance. To this end, the applicant proposed the following technical solution:
[0027] Experimental Example 1 Effect of different particle sizes on dissolution
[0028] The applicant prepared tablets of bictegravir and bictegravir sodium of different particle sizes according to the preparation method of Example 1 and conducted dissolution tests. There were 6 samples in each group, and the average value and standard deviation were calculated. The test conditions were: using USP apparatus II in 250 mL of fed simulated intestinal fluid ((FeSSIF, pH 6.5) at 37 ° C and a paddle speed of 100 rpm for 15 min. The results are shown in Table 1.
[0029] Table 1 Effect of different particle sizes on dissolution
[0030]
[0031] According to Table 1, the particle size of bictegravir sodium is 90 The dissolution rate within 15 minutes was significantly increased in the range of about 200 μm or less, and the dissolution rate hardly changed with the change of particle size; however, when the particle size D of bictegravir sodium 90 When the particle size is 10 μm or less, although the compound tablet has good dissolution, the fluidity of bictegravir sodium is poor and it is not suitable for large-scale production of tablets. Since bictegravir is a weakly acidic substance, its solubility in a pH-acidic environment is lower than that of bictegravir sodium. The solubility under the same conditions is low and varies greatly with the particle size, which will affect the quality uniformity of the tablets. In summary, the appropriate particle size of bictegravir sodium can be in the range of about 10-200 μm.
[0032] Experimental Example 2 Effect of disintegrant on adsorption rate of bictegravir sodium
[0033] The triple compound tablets were prepared using different disintegrants in the dosage and process of Example 1, and the content of bictegravir sodium was calculated by peak area according to the external standard method and the recovery rate was calculated. The detection conditions were: using USP apparatus II in 333 mL of fasting simulated intestinal fluid (pH 5.5) at 37° C. and a paddle speed of 100 rpm for 15 min. The results are shown in Table 1. The detection method of bictegravir sodium is prior art and will not be described in detail here.
[0034] Table 2 Effect of different disintegrants on the adsorption rate of bictegravir sodium
[0035]
[0036] As shown in Table 2, the main drug recovery rates of sodium carboxymethyl starch and cross-linked polyvinylpyrrolidone are both lower than 95%, while the recovery rate of the commonly used cross-linked sodium carboxymethyl cellulose is 97%, which also has a certain adsorption effect on the main drug. The main recovery rate of low-substituted hydroxypropyl cellulose is 101%, which can effectively avoid the adsorption of the main drug and reach the recovery rate standard of 98-102%.
[0037] Example 1
[0038] A triple compound tablet comprising the following ingredients:
[0039]
[0040]
[0041] Prepared by the following method:
[0042] S1, material handling on the first floor
[0043] The prescribed amount of bictegravir sodium and polyvinyl alcohol were ultrafinely ground to 50 μm, mixed for 8 min, hot melt extruded at 78 °C, cooled to room temperature and ground to D 90 The first particles are 150 μm in size; the first particles, microcrystalline cellulose, cross-linked sodium carboxymethyl cellulose and magnesium stearate are mixed for 4 minutes and then set aside;
[0044] S2, material handling on the second floor
[0045] The prescribed amount of emtricitabine, tenofovir alafenamide hemifumarate, microcrystalline cellulose, and cross-linked sodium carboxymethyl cellulose were mixed for 5 minutes and then dry granulated. After granulation, the granules were passed through a 60 mesh, and magnesium stearate was added and mixed for 3 minutes for later use;
[0046] S3, tableting, coating
[0047] 1000 double-layer tablets are pressed by using the mixture containing bictegravir sodium as the first layer and the mixture containing emtricitabine and tenofovir alafenamide hemifumarate as the second layer, and then dried after coating.
[0048] Example 2
[0049] A triple compound tablet comprising the following ingredients:
[0050]
[0051]
[0052] Prepared by the following method:
[0053] S1, material handling on the first floor
[0054] The prescribed amount of bictegravir sodium and polyvinyl alcohol were ultrafinely ground to 100 μm, mixed for 5 min, and then hot-melt extruded at 80 °C. After cooling to room temperature, the mixture was ground to D 90 The first particles are 100 μm in size; the first particles, microcrystalline cellulose, low-substituted hydroxypropyl cellulose and hydrogenated vegetable oil are mixed for 5 minutes and then set aside;
[0055] S2, material handling on the second floor
[0056] The prescribed amount of emtricitabine, tenofovir alafenamide hemifumarate, microcrystalline cellulose, and low-substituted hydroxypropyl cellulose were mixed for 8 minutes and then dry granulated. After granulation, the granules were passed through a 60 mesh, and hydrogenated vegetable oil was added and mixed for 5 minutes for later use;
[0057] S3, tableting, coating
[0058] 1000 double-layer tablets are pressed by using the mixture containing bictegravir sodium as the first layer and the mixture containing emtricitabine and tenofovir alafenamide hemifumarate as the second layer, and then dried after coating.
[0059] Example 3
[0060] A triple compound tablet comprising the following ingredients:
[0061]
[0062] Prepared by the following method:
[0063] S1, material handling on the first floor
[0064] The prescribed amount of bictegravir sodium and polyvinyl alcohol were ultrafinely ground to 80 μm, mixed for 8 min, hot melt extruded at 76 °C, cooled to room temperature and ground to D 90The first particles are 200 μm in size; the first particles, microcrystalline cellulose, low-substituted hydroxypropyl cellulose and sodium stearyl fumarate are mixed for 4 minutes and then set aside;
[0065] S2, material handling on the second floor
[0066] The prescribed amount of emtricitabine, tenofovir alafenamide hemifumarate, microcrystalline cellulose, and low-substituted hydroxypropyl cellulose were mixed for 5 minutes and then dry granulated. After granulation, the granules were passed through a 60 mesh, and then sodium stearyl fumarate was added and mixed for 3 minutes for later use;
[0067] S3, tableting, coating
[0068] 1000 double-layer tablets are pressed by using the mixture containing bictegravir sodium as the first layer and the mixture containing emtricitabine and tenofovir alafenamide hemifumarate as the second layer, and then dried after coating.
[0069] Example 4
[0070] A triple compound tablet comprising the following ingredients:
[0071]
[0072] Prepared by the following method:
[0073] S1, material handling on the first floor
[0074] The prescribed amount of bictegravir sodium and polyvinyl alcohol were ultrafinely ground to 50 μm, mixed for 8 min, hot melt extruded at 78 °C, cooled to room temperature and ground to D 90 The first particle size is 150 μm; the prescribed amount of microcrystalline cellulose and sodium carboxymethyl cellulose are mixed for 10 minutes, and then an appropriate amount of water is added for wet granulation. After drying, the particles are sized to obtain a particle size D 90 The second particle is 150 μm; the first particle, the second particle, low-substituted hydroxypropyl cellulose and glyceryl behenate are mixed for 4 minutes and then set aside;
[0075] S2, material handling on the second floor
[0076] 80% of the prescribed amount of emtricitabine and the prescribed amount of tenofovir alafenamide hemifumarate, microcrystalline cellulose PH113, and low-substituted hydroxypropyl cellulose were mixed for 10 minutes and then dry granulated to obtain an average particle size D 90 = 150 μm third particles, the third particles, the remaining amount of emtricitabine and behenic acid glyceryl are mixed for 3 minutes for use;
[0077] S3, tableting, coating
[0078] 1000 double-layer tablets are pressed by using the mixture containing bictegravir sodium as the first layer and the mixture containing emtricitabine and tenofovir alafenamide hemifumarate as the second layer, and then dried after coating.
[0079] Comparative Example 1
[0080] The same components as in Example 4 were used for preparation, with the only difference being that the prescribed amount of bictegravir sodium and polyvinyl alcohol were not subjected to hot melt extrusion but directly mixed with the lubricant, that is, the material of the first layer was processed by the following method:
[0081] The prescribed amount of bictegravir sodium and polyvinyl alcohol were ultrafinely ground to 50 μm and set aside; the prescribed amount of microcrystalline cellulose and sodium carboxymethyl cellulose were mixed for 10 minutes, and then an appropriate amount of water was added for wet granulation. After drying, the particles were granulated to obtain a particle size of D 90 The second particles are 150 μm; the second particles, bictegravir sodium, polyvinyl alcohol, low-substituted hydroxypropyl cellulose and behenic acid glyceryl are mixed for 4 minutes and then set aside.
[0082] Comparative Example 2
[0083] Commercially available Bituowei, produced by Gilead
[0084] The tablets prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to dissolution tests on bicletegravir sodium, respectively. The test conditions were: using USP apparatus II in 250 mL of fed simulated intestinal fluid (FESSIF, pH 6.5) at 37°C and a paddle speed of 100 rpm. The results are shown in Table 3.
[0085] Table 3 Dissolution test results
[0086]
[0087]
[0088] As shown in Table 3, the use of cross-linked sodium carboxymethyl cellulose as a disintegrant in Example 1 can make the triple compound tablets disintegrate quickly. Since bictegravir sodium is subjected to hot melt extrusion treatment with polyvinyl alcohol after ultrafine grinding, the solubility at 15 minutes is 57.1% and is slightly faster than that of Comparative Example 2, and the solubility of bictegravir sodium at 60 minutes is equivalent to that of Comparative Example 2. The reason may be that cross-linked sodium carboxymethyl cellulose has adsorption to bictegravir sodium, resulting in the final solubility being slightly lower than that of Comparative Example 2; while in Examples 2-4, low-substituted hydroxypropyl cellulose is used as a disintegrant, and bictegravir sodium is subjected to hot melt extrusion treatment with polyvinyl alcohol after ultrafine grinding, resulting in a solubility at 15 minutes that is equivalent to that of Comparative Example 2, and there is no sudden release of drug; wherein in the first layer of Example 4, microcrystalline cellulose is first wet-granulated with sodium carboxymethyl cellulose to obtain the second granules and then mixed with other components, which can further improve the solubility of bictegravir sodium. In Comparative Example 1, since bictegravir sodium and polyvinyl alcohol were not hot-melt extruded but directly mixed with other ingredients, the final dissolution rate was significantly lower than that of Comparative Example 2, but the experimental data fluctuated greatly, indicating that bictegravir sodium itself was difficult to mix evenly due to high static electricity after being ultrafinely powdered. Emtricitabine and tenofovir alafenamide hemifumarate have good solubility. The two ingredients in the tablets were prepared using USP apparatus II, and at least 90% could be released in 500 ml of 50 mM sodium citrate with a pH of 5.5 at 37°C and a paddle speed of 75 RPM for 20 min.
[0089] In addition, the tablets prepared in Example 4 and Comparative Example 2 were placed under accelerated conditions (40°C-RH75%) for 3 months, and the corresponding total impurity contents of tenofovir alafenamide hemifumarate were 0.85% and 2.24%, respectively, while the stability of tenofovir alafenamide hemifumarate in Examples 1-3 was equivalent to that of Comparative Example 2. For the materials of the second layer, in Example 4, by directly adding part of emtricitabine during the mixing process, the proportion of tenofovir alafenamide hemifumarate in the local environment of the third granules was increased while meeting the normal tableting requirements, and the contact probability of tenofovir alafenamide hemifumarate and emtricitabine was reduced to further improve its stability; at the same time, when the sodium chloride: microcrystalline cellulose pH113 in the third granules is 1:3, the stability of tenofovir alafenamide hemifumarate can be further improved.
[0090] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A triple compound tablet, characterized in that: The invention comprises a first layer and a second layer, wherein the first layer comprises 50-55 parts of bictegravir sodium and has a particle size D 90 The invention discloses a novel nanostructured film having a thickness of 10-200 μm, 16-20 parts of polyvinyl alcohol, 220-240 parts of a filler, 20-30 parts of a disintegrant, and 2-8 parts of a lubricant. The second layer comprises 190-210 parts of emtricitabine, 25-30 parts of tenofovir alafenamide hemifumarate, 110-125 parts of a filler, 20-30 parts of a disintegrant, and 2-8 parts of a lubricant.
2. The triple compound tablet according to claim 1, characterized in that: The first layer includes 51-53 parts of bictegravir sodium and a particle size D 90 The invention discloses a novel nanostructured film having a particle size of 50-150 μm, 16-20 parts of polyvinyl alcohol, 225-233 parts of a filler, 21-25 parts of a disintegrant, and 3-6 parts of a lubricant. The second layer comprises 195-205 parts of emtricitabine, 26-29 parts of tenofovir alafenamide hemifumarate, 110-119 parts of a filler, 24-27 parts of a disintegrant, and 4-7 parts of a lubricant.
3. The triple compound tablet according to claim 1 or 2, characterized in that: The disintegrant is any one of sodium carboxymethyl starch, low-substituted hydroxypropyl cellulose, cross-linked sodium carboxymethyl cellulose, cross-linked polyvinylpyrrolidone, and starch.
4. The triple compound tablet according to claim 1 or 2, characterized in that: The filler comprises at least one of pregelatinized starch, lactose, mannitol, sorbitol, sucrose, microcrystalline cellulose, calcium hydrogen phosphate and sodium chloride.
5. The triple compound tablet according to claim 1 or 2, characterized in that: The lubricant is any one of magnesium stearate, calcium stearate, stearic acid, hydrogenated vegetable oil, stearyl palmitin, glyceryl behenate, sodium stearyl fumarate, colloidal silicon dioxide and talc.
6. The triple compound tablet according to claim 1, characterized in that: The total weight of the tablet is 680-720 mg / tablet.
7. The method for preparing the triple compound tablet according to any one of claims 1 to 6, characterized in that: include: S1, Material handling on the first floor The prescribed amount of bictegravir sodium and polyvinyl alcohol were ultrafinely ground to D 90 =50-150μm, mix for 5-15min, hot melt extrude at 75-80℃, cool to room temperature and crush to D 90 = First particles of 50-150 μm; Mix the first particles, filler, disintegrant and lubricant oil for 3-10 minutes and set aside; S2, material handling on the second floor Mix the prescribed amount of emtricitabine, tenofovir alafenamide hemifumarate, filler, disintegrant, and lubricant for later use; S3, tableting, coating A double-layer tablet is compressed by using a mixture containing bictegravir sodium as the first layer and a mixture containing emtricitabine and tenofovir alafenamide hemifumarate as the second layer, and then dried after coating.
8. The method for preparing the triple compound tablet according to claim 7, characterized in that: Step S2 comprises: dry granulating the emtricitabine, tenofovir alafenamide hemifumarate, filler and disintegrant in the prescribed amount for 8-12 minutes, mixing with lubricant for 3-10 minutes after granulation, or mixing 80-90% of the prescribed amount of emtricitabine and the prescribed amount of tenofovir alafenamide hemifumarate, filler and disintegrant for 8-12 minutes, dry granulating the emtricitabine, mixing with lubricant and the remaining amount of emtricitabine for 3-10 minutes after granulation.
9. The method for preparing the triple compound tablet according to claim 7, characterized in that:
10. In step S3, the coating material accounts for 2.5-3.2% of the total weight of the tablet and the coating material is any one of hydroxypropyl methylcellulose, methylcellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose.
Citation Information
Patent Citations
Therapeutic compositions for treatment of human immunodeficiency virus
CN108348473A
Pharmaceutical composition comprising emtricitabine, tenofovir and bicotegravir
CN117653634A
Solid composition comprising propofol tenofovir and / or bicotegravir
CN118414146A
Tablet compositions comprising bictegravir, tenofovir alafenamide and emtricitabine
IN201841012398A
Therapeutic Compositions for Treatment of Human Immunodeficiency Virus
US20170189337A1
